Illiquidity, insolvency, and banking regulation - Jin Cao (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2010)
This paper provides a compact framework for banking regulation analysis in the presence of uncertainty between systemic liquidity and solvency shocks. Extending the work by Cao & Illing (2009a, b), it is shown that systemic liquidity shortage arises endogenously as part of the inferior mixed strategy equilibrium. The paper compares dierent traditional regulatory policies which intend to fix the ineciencies, and argues that the co-existence of illiquidity and insolvency problems adds extra cost for banking regulation and makes some schemes that are optimal under pure illiquidity risks (such as liquidity regulation with lender of last resort policy) fail. The regulatory cost can be minimized by combining the advantages of several instruments.
urn:nbn:de:bvb:19-epub-11370-3
Keywords: E5; G21; G28; 330; liquidity risk; insolvency risk; liquidity regulation; equity requirement; Liquidität; Insolvenz; Systemrisiko; Finanzkrise; Bankrisiko; Bankenliquidität; Bankenaufsicht; Basler Akkord; Theorie